Women Investors' Perception Towards Investment-An Empirical Study - Gnana Desigan, C; Kalaiselvi, S.; Anusuya, L. (Indian Journal of Marketing, 2006)
The hand that rocks the cradle rules the world's is a popular saying about women. Savings is a habit specially embodied to women. Even in the past, when women mainly depend on their spouse income, they used to save to meet emergencies as well as for future activities. In those days, women did not have any awareness about various investment outlets. But as time passed, the scenario has totally changed.